Engaging imagination : helping students become creative and reflective thinkers - James, Alison, 1960-; Brookfield, Stephen (New York : John Wiley & Sons, 2014)
'How to nurture creativity in tomorrow's innovators--today's college students. When asked what they want colleges to emphasize most, employers didn't put science, computing, math, or business management first. According to AAC&U's 2013 employer survey, 95% of employers give hiring preference to college graduates with skills that will enable them to contribute to innovation in the workplace. In Engaging Imagination: Helping Students Become Creative and Reflective Thinkers, two leading educators help college instructors across disciplines engage students in nurturing creativity and innovation for success beyond the classroom. Alison James, an expert in creative arts education, and Stephen D. Brookfield, Distinguished University Professor of Education, outline how creative exploration can extend students' reflective capabilities in a purposeful way, help them understand their own potential and learning more clearly, and imbue students with the freedom to generate and explore new questions. This book: shows why building creative skills pays dividends in the classroom and in students' professional lives long after graduation; offers research-based, classroom-tested approaches to cultivating creativity and innovation in the college setting; provides practical tools for incorporating'play' into the college curriculum; draws on recent advances in the corporate sector where creative approaches have been adopted to reinvigorate thinking and problem-solving processes; and includes examples from a variety of disciplines and settings. Engaging Imagination is for college and university faculty who need to prepare students for the real challenges of tomorrow's workplace'--
Includes bibliographical references and index.
Keywords: Creative thinking -- Study and teaching; Reflective learning -- Study and teaching